2021
DOI: 10.1101/2021.08.20.457082
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A nitrite-oxidizing bacterium constitutively consumes atmospheric hydrogen

Abstract: Chemolithoautotrophic nitrite-oxidizing bacteria (NOB) of the genus Nitrospira contribute to nitrification in diverse natural environments and engineered systems. Nitrospira are thought to be well-adapted to substrate limitation owing to their high affinity for nitrite and capacity to use alternative energy sources. Here, we demonstrate that the canonical nitrite oxidizer Nitrospira moscoviensis oxidizes hydrogen (H2) below atmospheric levels using a high-affinity group 2a nickel-iron hydrogenase [Km(app) = 32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…More recently, several high-affinity lineages of group 1 and 2 [NiFe]-hydrogenases have been identified that input atmospheric H 2 -derived electrons into the aerobic respiratory chain [4,5,21,29,30]. Whole-cell studies suggest these enzymes have a significantly higher apparent affinity for H 2 (K m 30 to 200 nM) and appear to be insensitive to inhibition by O 2 [4,5,10,12,13,31,32]. However, given these hydrogenases have yet to be isolated, it remains unknown how they have evolved to selectively oxidize H 2 , tolerate exposure to O 2 , and interact with the electron transport chain.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, several high-affinity lineages of group 1 and 2 [NiFe]-hydrogenases have been identified that input atmospheric H 2 -derived electrons into the aerobic respiratory chain [4,5,21,29,30]. Whole-cell studies suggest these enzymes have a significantly higher apparent affinity for H 2 (K m 30 to 200 nM) and appear to be insensitive to inhibition by O 2 [4,5,10,12,13,31,32]. However, given these hydrogenases have yet to be isolated, it remains unknown how they have evolved to selectively oxidize H 2 , tolerate exposure to O 2 , and interact with the electron transport chain.…”
Section: Introductionmentioning
confidence: 99%